Influence of PGPR, Bio-Phosphate Microorganism and Phosphate on Growth of Oil Palm Seedlings Under Drought Stress Conditions - Suryanti, Sri; Umami, Arif; Gunawan, Sri; Santi, Idum Satia; Maulana, Reza Hadi (KnE Life Sciences, 2022)
Drought is a major abiotic stress that threatens the production of agricultural oil palms. Drought interferes with plant uptake of phosphorus. The goal of this study was to investigate how plant growth-promoting rhizobacteria (PGPR), bio-phosphate microorganisms, and phosphate affected oil palm growth under drought stress. The study was conducted at the Tri Dharma Research Station INSTIPER in Yogyakarta from January to May 2020, and it used a factorial and completely randomized design with two factors and three replicates per treatment. The first factor was a fertilization treatment that included P1 (PGPR), P2 (bio-phosphate microorganisms), P3 (phosphate). The second factor was a drinking interval of L1 (once per day) and L2 (once per seven days). At 120 days after planting, data were collected. The results showed that the PGPR, bio-phosphate microorganisms and phosphate had no significant effect on plant height, number of leaves, leaf area, chlorophyll content, dry weight of plants, volume of root, dry weight of root and shoot, stem diameter, number of stomata, and root-shoot ratio. Root volume, root dry weight, and root-shoot ratio were significantly affected by one-day and seven-day watering intervals. Phosphate fertilization with watering once every seven days considerably increased the width of the stomata openingsI Keywords: PGPR, Bio-Phosphate, Phosphate, Oil Palm, Drought